Transverse Movement Kinetics of a Unit for Inter-Row Crops—Case Study: Cultivator Unit. - Findura, Pavol; Nadykto, Volodymyr; Надикто, Володимир Трохимович; Kyurchev, Volodymyr; Кюрчев, Володимир Миколайович; Gierz, Łukasz (My University, 2024)
ENG: Due to the negative impact of chemical inter-row weed control on the environment, mechanical weed control is increasingly used in practice. Machine-tractor units (MTU) are used with the row cultivator’s rear and frontal central position for its implementation. We have designed a unit in which side cultivators are used along with the central one. This paper considers the transverse movement kinematics of such an MTU’s outside right and left cultivators’ working devices in the horizontal plane. The present emulation of side machines is made by changing the longitudinal coordinate of their location relative to the tractor’s front and rear axles. Calculations have established that the frontal cultivator responds more intensively to the control action by changing the turning angle of the tractor’s steering wheels. However, if the value of this parameter is less than 2.75◦, a rear-mounted cultivator is preferred, because in this case, the values of lateral deviations for the external, left, and right working device are smaller. When the turning angle of tractor wheels is from 1◦ to 3◦ (typical for MTU row work), a threefold increase in the working width of the cultivator causes a slight antiphase deviation in its external working devices (an increase or decrease in the amplitude of these deviations does not exceed 4%). The model that we have developed allows us to select the values of the MTU design parameters for which the lateral displacement will be very small (close to zero). As the turning angle of the tractor wheels increases to 3◦, the external left and right working devices of the cultivators react inversely. This means that in the case of the rear machine, the values of lateral displacements increase, while in the case of the front machine, they decrease. At a turning angle of the tires of the tractor wheels close to 2.5◦, the lateral displacements for the rear and front machines are the same.//////////////////////// UKR :У зв'язку з негативним впливом хімічної міжрядної боротьби з бур'янами на навколишнє середовище на практиці все частіше використовується механічна боротьба з бур'янами. Машинно-тракторні агрегати (МТУ) використовуються з заднім і фронтальним центральним розташуванням культиватора для його виконання. Ми спроектували агрегат, в якому поряд з центральним використовуються бічні культиватори. У роботі розглянута кінематика поперечного переміщення зовнішніх правих і лівих робочих пристроїв культиваторів МТУ в горизонтальній площині. Справжня емуляція бічних машин проводиться за рахунок зміни поздовжньої координати їх розташування щодо передньої і задньої осі трактора. Розрахунками встановлено, що фронтальний культиватор більш інтенсивно реагує на керуючу дію за рахунок зміни кута повороту рульових коліс трактора. Однак, якщо значення цього параметра менше 2,75°, перевага віддається задньому культиватору, тому що в цьому випадку значення бічних відхилень для зовнішнього, лівого і правого робочого пристрою менше. При куті повороту коліс трактора від 1° до 3° (характерно для рядних робіт МТУ) трикратне збільшення ширини захвату культиватора викликає незначне протифазне відхилення в його зовнішніх робочих пристроях (збільшення або зменшення амплітуди цих відхилень не перевищує 4%). Розроблена нами модель дозволяє підбирати значення конструктивних параметрів МТУ, при яких бічне зміщення буде дуже малим (близьким до нуля). При збільшенні кута повороту коліс трактора до 3° зовнішні лівий і правий робочі пристрої культиваторів реагують обернено. Це означає, що у випадку з задньою машиною значення бічних зміщень збільшуються, тоді як у випадку з передньою машиною вони зменшуються. При куті повороту шин тракторних коліс близько 2,5° бічні зміщення для задніх і передніх машин однакові.
Кінетика поперечного переміщення агрегату для міжрядних культур — приклад з практики: блок культиватора.
Keywords: row cultivator; working devices; turning angle of tractor wheels; yaw angle; просапний культиватор; робочі пристрої; кут повороту коліс трактора; кут рискання